Glycogenic acanthosis on mouth clinically present as white plaque - Schulz, Maykon Kennedy; Biancardi, Mariel Ruivo; Fernandes, Darcy; Almeida, Luciana Yamamoto De; Bufalino, Andreia; Leon, Jorge Esquiche (Faculdade São Leopoldo Mandic, 2018)
ABSTRACT Glycogenic acanthosis is a benign condition, commonly observed during endoscopic procedures in older patients, which present as slightly elevated whitish plaques often on the lower third of the oesophagus. Microscopically, glycogenic acanthosis is composed of hyperplastic squamous epithelium with intracytoplasmic glycogen deposits. The extraoesophageal glycogenic acanthosis is extremely rare, with only three case reports in the English-language literature. We report a white lesion showing glycogenic acanthosis-like features located on the left posterolateral border of the tongue, affecting a 56-year-old male patient. The medical history was non-contributory and the patient did not show any lesions during endoscopic examination of the oesophagus, stomach, and upper duodenum. Glycogenic acanthosis is a benign condition, which should be included in the differential diagnosis when assessing oral white lesions. It is important also to recognize this benign condition early and rule out the possibility of other more severe diseases, but further studies were necessary for better define their potential for persistence or recurrence, as observed in the current case.

RESUMO A acantose glicogênica é uma condição benigna, comumente observada durante procedimentos endoscópicos em pacientes idosos, e se apresenta como placas brancas levemente elevadas, freqüentemente encontrada no terço inferior do esôfago. Microscopicamente, a acantose glicogênica é composta por epitélio escamoso hiperplásico com depósitos de glicogênio intracitoplasmático. A acantose glicogênica extra-esofágica é extremamente rara, com apenas três relatos de casos na literatura em língua inglesa. Apresentamos um caso com uma lesão branca diagnosticada como acantose glicogênica, localizada na borda póstero-lateral esquerda da língua, afetando um paciente do sexo masculino de 56 anos. A história médica não foi contribuitória e o paciente não apresentou lesões durante o exame endoscópico do esôfago, estômago e duodeno superior. A acantose glicogênica é uma condição benigna, que deve ser incluída no diagnóstico diferencial na avaliação de lesões brancas orais. É importante também reconhecer precocemente essa condição benigna e descartar a possibilidade de outras doenças mais graves, porém mais estudos são necessários para melhor definir seu potencial de persistência ou recorrência, como observado no presente caso.
Acantose glicogênica na boca clinicamente presente como placa branca
Keywords: Diagnosis, differential; Glycogen; Mouth mucosa; Diagnóstico diferencial; Glicogênio; Mucosa Bucal